Association between subjective evaluation and physical parameters for radiographic images optimization - Alves, A. F. F. [UNESP]; Alvarez, M. [UNESP]; Ribeiro, S. M. [UNESP]; Duarte, S. B.; Miranda, J. R. A. [UNESP]; Pina, D. R. [UNESP] (Elsevier B.V., 2016)
Purpose: The purpose of this study was to develop a methodology to optimize computed radiographic techniques to image the skull, chest, and pelvis of a standard patient. Methods: Optimization was performed by varying exposure levels with different tube voltages to generate images of an anthropomorphic phantom. Image quality was evaluated using visual grading analysis and measuring objective parameters such as the effective detective quantum efficiency and the contrast-to-noise ratio. Objective and subjective evaluations were compared to obtain an optimized technique for each anatomic region. Results: Gold standard techniques provided a significant reduction in X-ray doses compared to the techniques used in our radiology service, without compromising diagnostic accuracy. They were chosen as follows 102 kVp/1.6 mAs for skull; 81 kVp/4.5 mAs for pelvis and 90 kVp/3.2 mAs for chest. Conclusion: There is a range of acceptable techniques that produce adequate images for diagnosis in computed radiography systems. This aspect allows the optimization process to be focused on the patient dose without compromising diagnostic capabilities. This process should be performed through association of quantitative and qualitative parameters, such as effective detective quantum efficiency, contrast-to-noise ratio, and visual grading analysis. (C) 2015 Associazione Italiana di Fisica Medica. Published by Elsevier Ltd. All rights reserved.
Keywords: Radiology; Computed radiography; Image quality; Dose